2017
DOI: 10.1016/j.neurobiolaging.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Different trajectories of decline for global form and global motion processing in aging, mild cognitive impairment and Alzheimer's disease

Abstract: The visual processing of complex motion is impaired in Alzheimer's disease (AD). However, it is unclear whether these impairments are biased toward the motion stream or part of a general disruption of global visual processing, given some reports of impaired static form processing in AD. Here, for the first time, we directly compared the relative preservation of motion and form systems in AD, mild cognitive impairment, and healthy aging, by measuring coherence thresholds for well-established global rotational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
(108 reference statements)
1
12
0
Order By: Relevance
“…Most studies indeed compared thresholds between just two age groups, i.e., between younger adults, typically aged between 18 and 30 years, and older adults, typically older than 60 years. Findings often show substantial age-related increase in coherence thresholds (Allen, Hutchinson, Ledgeway, & Gayle, 2010;Andersen & Atchley, 1995;Atchley & Andersen, 1998;Gilmore, Wenk, Naylor, & Stuve, 1992;Snowden & Kavanagh, 2006;Wojciechowski, Trick, & Steinman, 1995; but see also Porter et al, 2017). Moreover, speed discrimination (Genova & Bocheva, 2013;Norman, Ross, Hawkes, & Long, 2003) as well as motion direction discrimination (Ball & Sekuler, 1986;Bennett et al, 2007;Bocheva, Angelova, & Stefanova, 2013;Bogfjellmo et al, 2013) have been found to decline with increasing age.…”
Section: Global Motion Processingmentioning
confidence: 94%
See 2 more Smart Citations
“…Most studies indeed compared thresholds between just two age groups, i.e., between younger adults, typically aged between 18 and 30 years, and older adults, typically older than 60 years. Findings often show substantial age-related increase in coherence thresholds (Allen, Hutchinson, Ledgeway, & Gayle, 2010;Andersen & Atchley, 1995;Atchley & Andersen, 1998;Gilmore, Wenk, Naylor, & Stuve, 1992;Snowden & Kavanagh, 2006;Wojciechowski, Trick, & Steinman, 1995; but see also Porter et al, 2017). Moreover, speed discrimination (Genova & Bocheva, 2013;Norman, Ross, Hawkes, & Long, 2003) as well as motion direction discrimination (Ball & Sekuler, 1986;Bennett et al, 2007;Bocheva, Angelova, & Stefanova, 2013;Bogfjellmo et al, 2013) have been found to decline with increasing age.…”
Section: Global Motion Processingmentioning
confidence: 94%
“…The contribution of cognitive resources to these differences is still largely unexplored. Interestingly, there is some evidence from clinical studies that deficits scale across a continuum of age-related cognitive changes observed in healthy aging, mild cognitive impairment, and dementia (Porter et al, 2017). More research is needed in order to clarify to which extent cognitive resources can explain changes in motion perception during aging.…”
Section: Cognitive Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[70]. Several assessment approaches have been examined as screening tests for MCI; most focusing on memory testing [11,[71][72][73][74], as well as for making a diagnosis of MCI [7,23,[75][76][77]. However, the MCI diagnosis is crude and not well implemented clinically.…”
Section: Screening For Mild Cognitive Impairment (Mci)mentioning
confidence: 99%
“…With progressively increasing attention to MCI, more precise assessment technologies are being developed for when an individual lies on the temporal trajectory from normal to dementia [55,76,78,79], and such improved approaches are being suggested for measuring the progressive decline of cognitive function associated with early AD as well as assessing the benefits of intervention trials [13-15, 75, 80].…”
Section: Screening For Mild Cognitive Impairment (Mci)mentioning
confidence: 99%